Rituals of care: Strategies adopted by HIV testers to avoid misdiagnosis in rapid HIV testing in Zimbabwe. Issue 12 (2nd December 2022) - Beckmann, Nadine; Skovdal, Morten; Maswera, Rufurwokuda; Nyamukapa, Constance; Gregson, Simon
ABSTRACT: A growing number of studies highlight high levels of misdiagnosis in the scale-up of HIV rapid testing programmes, which often remain invisible to individual testers. Drawing on interviews with HIV testers and observations in four health facilities in Zimbabwe, we show that testers navigated the translation of the standardised, dis-embodied norms of laboratory-based testing into the body work of point-of-care testing through ritualisation of laboratory-practices in their daily clinical work. Yet, this was interrupted through the challenging work conditions the testers face. They ritualised careful procedures, forcing themselves to focus even if queues were long, and making quality assurance procedures part of their daily routine. They actively tried to reduce their workloads and double-checked and discussed unexpected results, especially when a test result did not match their evaluation of clients' circumstances or clinical status. This helped not only to increase confidence in the authenticity of their diagnosis, but also to share responsibility for potential errors. Existing approaches to tackle the problem of misdiagnosis through quality assurance (QA) procedures mainly focus on adjusting individual testers' performance and ensuring that basic testing resources were present, thus falling short of creating a work environment that is conducive to high quality testing.